Comparative study on the daily activity budget of sun bear (Helarctus malayanus) in captivity and semi-captivity - Siti Sarayati Abdul Mawah; Lo, Chor-Wai; Farnidah Jasnie (Penerbit Universiti Kebangsaan Malaysia, 2021)
A comparative study on the daily activity budget of the sun bear was conducted in Lok Kawi Wildlife Park and Borneon Sun Bear Conservation Centre (BSBCC) Malaysia. The behaviour of 22 individuals was recorded using the Instantaneous scan sampling method. A total of 330 hr were collected, with 180 hr were collected at Lok Kawi Wildlife Park and 150 hr at BSBCC. Thirteen behavioural activities were recorded using the Ad-libitum sampling method in both captive and semicaptive bears, which were then grouped into three categories; active, passive, and abnormal behaviours classes and tabulated in an ethogram. Captive sun bears are kept permanently under human control, such as in zoos, while semi-captive sun bears are released to the forest during the day but kept in the cage at night. This study shows that semi-captive bears are significantly more active than captive bears. More passive and abnormal behaviours are present in captive bears. Stereotypic pacing scored the highest percentage of observation with 24% for abnormal behaviour in captive bears. Both captive and semi-captive bears showed a similar pattern of active and passive behavioural rhythms. The peak for active behaviours was from 1000 to 1100 hr, and the peak for passive behaviours was from 1300 to 1400 hr. In conclusion, although there was a difference in activities done between captive and semi-captive bears, the pattern of behavioural rhythms between both group of bears was similar. The introduction of enrichment programmes is crucial to captive bears to reduce stereotypic pacing behaviour.